2017
DOI: 10.1016/j.scitotenv.2016.09.102
|View full text |Cite
|
Sign up to set email alerts
|

Solar ultraviolet doses and vitamin D in a northern mid-latitude

Abstract: to 15% are similar in the defined interval measurements in relation to the whole UVA band.Regarding the PAR band, the model overestimates the direct normal irradiance of the PAR band by only 2.2%. With this, the results of the PAR band are more conclusive, as it has been found that for direct normal irradiance values higher than 280 W/m 2 the MBE error is almost zero and the other two estimator errors are small, about 5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…It was considered that vitamin D winter period ranges between November and February, since at latitudes above 40° N (latitude of Porto, where the study was conducted) sunlight appears not to be strong enough to the endogenous synthesis, from November to February. This is supported by other works performed at similar latitudes of Porto, namely in Boston (USA) [ 27 ] and in Valencia (Spain) [ 28 ]. During the other months of the year, the ultraviolet index in Porto is >3, being sufficient for the cutaneous production of vitamin D [ 29 ].…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…It was considered that vitamin D winter period ranges between November and February, since at latitudes above 40° N (latitude of Porto, where the study was conducted) sunlight appears not to be strong enough to the endogenous synthesis, from November to February. This is supported by other works performed at similar latitudes of Porto, namely in Boston (USA) [ 27 ] and in Valencia (Spain) [ 28 ]. During the other months of the year, the ultraviolet index in Porto is >3, being sufficient for the cutaneous production of vitamin D [ 29 ].…”
Section: Methodssupporting
confidence: 81%
“…Additional important results were the determinants of serum vitamin D status. As previously reported, more educated participants presented higher mean serum 25(OH)D concentration [ 43 ], as well as the subjects evaluated between March and October, reflecting the seasonal variation described for serum 25(OH)D [ 28 ]. Participants on the extreme categories (lower and higher) of BMI, had lower mean serum 25(OH)D concentration despite the fact that previous studies found an inverse association [ 36 , 44 ].…”
Section: Discussionsupporting
confidence: 58%
“…In a recent publication, the authors recommended: “… efforts should be made to maintain vitamin D status throughout the year by spending time outside regularly (without taking risks of sunburns and skin cancer) and paying attention to a healthy diet rich in vitamin D, especially during winter and spring” [ 46 ]. This is a representative example for many publications, and official statements in various countries which, although recognizing the health risks resulting from vitamin D deficiency, recommend activities which are ineffective in their translation into practice for various reasons: (1) due to lifestyle changes, children and adolescents are no longer involved in enough outdoor activities, as many publications confirm; (2) in Germany, as well as in various other European countries, even if enough time is spent outdoors, it would be impossible to produce sufficient vitamin D in the skin during half of the year (roughly from October to March) as sufficient solar UVB radiation is missing [ 2 , 52 ]; (3) it has been known for a long time (and is recalled by the same authorities in their statements) that dietary vitamin D intake provides only 5–10% of the recommendations, meaning that vitamin D dietary intake is negligible and vitamin D status cannot be improved by a healthy diet alone; (4) low storage of vitamin D in the liver and fat tissue are considered reasons for low 25(OH)D levels in winter and spring. If we take into account that body fat may store vitamin D, the question arises as to why obese individuals show a mean 35% and overweight individuals a mean 24% higher vitamin D deficiency status compared to average weight individuals, and why they must be considered as a high risk group for vitamin D deficiency [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure times to produce erythema were obtained to determine the skin cancer risk, and these were longer than the times required to obtain the recommended vitamin D daily dose. 62 Moderate sun exposure is important enough to synthetize vitamin D but not too much to increase the skin cancer risk.…”
Section: Vitamin Dmentioning
confidence: 99%